ACCESSIBILITY OF THE ENVIRONMENT TO DISADVANTAGED PEOPLE - Kitchoukova, Maria (Innovation in Woodworking Industry and Engineering design, 2021)
During past years the number of people with temporary and permanent disabilities has been constantly increasing. This trend turns the question for the accessibility of everyday living environment for the disadvantaged people into lively and important topic. This current study is motivated by the relevance of this problem and is based on analysis and comparison of recent and existing regulation in Bulgaria and different countries around the world. In order to support the results obtained and to gather additional information about the current situation, a survey was conducted among people with disabilities, the data from which was analyzed and the relevant conclusions were made.